A study on the importance of health insurance protection: the level of awareness among UiTM staff / Noorhayati Yusof Ali...[et al.] - Yusof Ali, Noorhayati; Abd Ghani, Roseziahazni; Mustafa, Fadhilah; Mohamad, Faizah (2007)
The main purpose of this study was to investigate the extent of awareness among UiTMT staff of the importance of health insurance and their participation in the purchase of the policy. The level of awareness of health insurance was investigated based on three selected determinants consisted of cost of medical treatment, financial security and health culturedness. The findings of this study revealed that the UiTMT staff had moderately high awareness of health insurance protection. Among the three determinant variables, the level of awareness was high in financial security followed by health culturedness and then by the cost of medical treatment. Overall, it can be concluded that those who have health insurance had high level of awareness in all variables investigated. However, they had significantly higher level of awareness in the cost of medical treatment and the overall awareness than those who are not insured. This means that respondents bought health insurance because they are aware of the importance of that policy, especially with regard to the cost of medical treatment.